Exploring the Development of Undergraduates’ Academic Literacy and Its Influencing Factors Based on Social Cognitive Theory - Ma, Xiulin; Wang, Jiayong; Sun, Xiaoxiao (Advances in Social Sciences Research Journal, 2026)
Academic literacy is a significant indicator to measure the academic development level of undergraduates and the construction of higher education in China. In order to analyze the current situation of the undergraduates’ academic literacy development and relevant key influencing factors, this study constructed a corresponding research model on influencing factors of academic literacy based on Social Cognitive Theory. To verify the proposed model and hypotheses, the study was conducted among undergraduate students of Beijing A University. This study found that: (1) The digital literacy and social network had significant positive impacts on academic literacy from the behavioral and environmental levels, respectively; (2) There was a significant positive mutual influence between digital literacy and social network; (3) Digital literacy and social network jointly formed two mediating paths affecting academic literacy. To further enhance the academic literacy of undergraduate students, the study offers the following suggestions for the cultivation of academic ability: (1) Great importance should be attached to the design of research processes; (2) The deep integration of digital literacy and academic literacy should be promoted; (3) A diversified and dynamic academic evaluation system should be improved to encourage students’ all-round development.